Effect of reseeding and cattle manure on pasture and livestock water productivity in rangelands of Nakasongola District, Uganda - Mugerwa, S. (Makerere University, 2009)
Rangeland degradation attributed to overgrazing, termite activity and deforestation has resulted in the development of large bare surfaces locally known as “Biharamata” in Nakasongola District. Devoid of adequate vegetation cover, the rangelands are associated with reduced water infiltration, accelerated runoff causing soil erosion, silting of downsteam water reservoirs and hence reduced livestock water productivity. This research was therefore aimed at improving livestock water productivity in rain-fed pastoral production systems through restoring vegetation on degraded bare surfaces. The effect of reseeding and cattle manure application on pasture productivity and the resultant impact of these interventions on livestock water productivity were investigated. Six treatments were studied- Fencing plus manuring (FM), Fencing only (FO), Fencing plus reseeding (FR), Fencing + manure left on soil surface + reseeding (FMR), Fencing + Manure incorporated in to the soil + reseeding (FMR1) and control (C) (no manuring, fencing and reseeding). Data on soil nutrient status and pasture productivity was collected over a period of one year covering two dry seasons and two wet seasons. In both seasons, the dry matter yield varied significantly (p < 0.05) with treatments. Highest mean dry matter yield (3820kg/ha) was recorded in fenced, manured and reseeded plots and lowest in the control and fenced only plots. Mean dry matter production (3300kg/ha) recorded for the manured plots was 125% higher than that (1470kg/ha) from non-manured plots. Treatment and season interaction led to significant (p < 0.05) changes in percentage bare ground and species richness. The lowest percentage bare ground (2.4%) was recorded in the wet season for fenced, manured and reseeded treatment. Generally, the percentage bare ground for non-manured plots was 5 and 2 times more than that for manured plots in the wet and dry seasons, respectively. Highest species richness (10 species per m2) was recorded in fenced, manured and reseeded plots. Regardless of the season, treatments caused significant differences in crude protein (CP) content and neutral detergent fibre (NDF). Highest pasture CP (9.7%) value was recorded in fenced, manured and reseeded plots and lowest (4%) in fenced only plots. The CP (9.4%) content for manured plots was 73% higher than that (5.5%) recorded for non-manured plots. Highest percentage of NDF (85%) was recorded in fenced only plots and lowest in fenced, manured and reseeded plots. Treatment and season interaction led to significant (p < 0.001) differences in organic matter digestibility (OMD). Highest OMD (65%) was recorded in fenced, manured and reseeded plots and lowest (37%) in fenced only plots. Increase in dry matter production led to improvement in livestock water productivity. Highest increment (31% increases) in livestock water productivity was recorded in fenced, manured and reseeded plots with dry matter yield of 7644kg/ha/yr. Inclusion of cattle manure during reseeding operations improves pasture and livestock water productivity in degraded rangelands. The intervention is particularly important in termite infested degraded rangelands where pasture establishment is usually limited by termite damage. The success of this intervention however, lies in the ability of pastoralists to work out mechanisms that will enable them combine their herds so as to quicken the process of manure deposition and to ensure that a large area is covered in a short time.